The contribution of the civic education class in developing the spirit of citizenship among- primary school students- From the point of view of primary school teachers - younes, Djamila (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2023)
The current study aimed to find out the extent of the contribution of the civic education class in the development of the spirit of citizenship among primary school students from the point of view of their teachers in primary education, and to reveal the extent of the contribution of the civic education class in the development of each of the physical, psychological and social civic sense of these students inside and outside the institution as behaviors that can be observed inside Society, and to achieve this goal, a questionnaire was prepared to measure the level of citizenship among primary school students from the point of view of primary education teachers, consisting of 3 dimensions (the physical dimension, the psychological dimension, and the civil social dimension). Each of these dimensions consists of 7 items. On a sample of 240 primary education teachers in several primary schools in the state of Djelfa, the appropriate approach for carrying out this study is the descriptive approach. After collecting and analyzing the data, the following results were reached: The civic education class contributes significantly to the development of the material sense of primary students from the point of view of primary education teachers The civic education class contributes significantly to the development of the national psychological sense of primary students from the point of view of primary education teachers The civic education class contributes significantly to the development of social and civic awareness of primary students from the point of view of primary education teachers The civic education class contributes significantly to the development of the spirit of citizenship for primary students from the point of view of primary education teachers.